2008
DOI: 10.1111/j.1442-2018.2008.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the health‐promoting lifestyles of nursing and non‐nursing students in Istanbul, Turkey

Abstract: Undertaking a health-related course at university can facilitate an awareness of health-promoting lifestyles. We carried out a descriptive and cross-sectional study with 1616 university students in Istanbul, Turkey. Students from the nursing schools were compared to those from the schools of social sciences using a Turkish version of the Health-promoting Lifestyle Profile (HPLP) II after a validation study. The nursing students had more positive health-promoting lifestyles than those of the non-nursing student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
77
1
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 31 publications
27
77
1
21
Order By: Relevance
“…Similar finding was reported in previous studies [14] [17]. The influence of the culture and belief system of Jordan society might help to maintain spiritual growth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar finding was reported in previous studies [14] [17]. The influence of the culture and belief system of Jordan society might help to maintain spiritual growth.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, a study by Hong [30] found that older students had a significant high level of overall health promotion life style, particularly, in stress management, self actualization, health responsibility, and nutrition domains. In the same line, other studies found that only the mean score of the health responsibility domain increased parallel to the age of participants [15] [17]. More studies are needed to understand the effect of age on health promoting behaviors.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although many studies have been published regarding health promoting behaviours in certain groups, such as health personnel (Beser et al, 2007) and university students (Can et al, 2008), published studies investigating healthy life-style behaviours in women (Altay, 2006) have been limited. Today's health perception comprises the attainment of behaviours promoting and protecting the health of the individual, family and society in general and accepting the reality of the importance of a healthy life-style promotion in all individuals and in women in special (Al Ma'aitah et al, 1999).…”
Section: Healthy Life-style Promoting Behaviour In Turkish Women Agedmentioning
confidence: 99%
“…In addition to these developmental changes and newfound responsibilities, university students have greater autonomy and control over their lifestyle than adolescents. This transition period is the time to establish healthy lifestyle behaviours (Ulla Díez and Pérez-Fortis, 2009;Tuğut and Bekar, 2008;Can, Ozdilli et al, 2008). Therefore, it is essential to understand and evaluate health-promoting behaviours among adolescents in order to promote their healthy growth.…”
Section: 2269 Health-promoting Lifestyle Behaviour For Cancer Prevenmentioning
confidence: 99%